MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MEWARNAI GAMBAR SEDERHANA PADA ANAK USIA 5-6 TAHUN DI TK KEMALA BHAYANGKARI 01 KUPANG KOTA - Tamelab, Maryance (Devotion: Jurnal Pengabdian Masyarakat, 2025)
The purpose of this study was to improve fine motor abilities in group B2 at TK Kemala Bhayangkari 01 Kupang Kota, which is located in Nangka Street No. 85, Oetete Village, Oebobo Subdistrict, Kupang City. The research was conducted over a two-month period, from May to June 2023. 15 children from group B2 at TK Kemala Bhayangkari 01 Kupang Kota participated in the study. The data was gathered through observation and review. According to the study's first cycle's findings, four children (26.66%) did not demonstrate any significant improvement in their fine motor skills, four children (26.66%) attained the level of fine motor development that the teachers had predicted, and four children (26.66%) displayed excellent fine motor development. Meanwhile, 3 children (26.66%) required further coaching. The capacity of the children to engage in coloring simple drawings improved in the second cycle, with 8 children (43.33%) demonstrating greater skills. Furthermore, there was an increase of 7 children (46.66%) in fine motor skills when participating in coloring activities. Based on the findings of the study, it is possible to conclude that simple coloring activities can improve the fine motor abilities of children aged 5–6 years at TK Kemala Bhayangkari 01 Kupang Kota.